STUDI ANALISIS PRAKTIK NOVASI PADA PEMBIAYAAN MURABAHAH DI BAITUL MAAL WAT TAMWIL MUAMALAH SYARI’AH TEBUIRENG JOMBANG - Kusuma, Miftakhul Ari; Afif, Abdullah; Muhammad (Irtifaq, 2023)
Abstract: This article discusses the practice of novation (debt renewal) in murabahah financing at BMT Muamalah Syariah'ah Tebuireng Jombang and a review of Islamic law regarding the practice of novation in murabahah financing at BMT Muamalah Syariah'ah Tebuireng Jombang. This research is empirical juridical research, with a statutory, conceptual and phenomenological approach and analyzed using deductive and descriptive methods. Primary legal materials from observations, interviews, documentation, library data. Secondary law is obtained from books, journals and related literature. The research results show that the practice of novation in murabahah financing carried out by BMT Muamalah Syari'ah Tebuireng Jombang is in the form of financing restructuring with the type of rescheduling which is generally the same as objective novation. The innovation practice carried out by BMT Muamalah Syariah'ah Tebuireng Jombang is in accordance with Islamic law and its implementation cannot be separated from the decision of Bank Indonesia Regulation Number 13/9/PBI/2011 concerning Amendments to Bank Indonesia Regulation Number 10/18/PBI/2008 concerning Financing Restructuring for Sharia Banks and Sharia Business Units. Keywords: Murabahah Financing, Novation.